Evaluating Pearl Millet Germplasm for Morphological and Biochemical Parameters: Characterization of pearl millet - Rathore, Madhurjit Singh; Tiwari, Sushma; Singh, Sangeeta; Yadav, Ravi; Dwivedi, Neeta; Nimmy, M. S. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during the kharif season (July-October, 2024) at Rajmata Vijayaraje Scindia Krishi Vishwa Vidyalaya, Gwalior, Madhya Pradesh, to assess genetic diversity among thirty pearl millet (Pennisetum glaucum L.) germplasm lines based on morphological and biochemical traits. Total elevan morphological observations including grain yield, dry fodder yield, days to 50% flowering, days to maturity, plant height, number of productive tillers, panicle length, panicle diameter, 1000 seed weight, plant population and seed set under bagging and four biochemical parameters including total protein, total soluble sugar, total phenolic contents and DPPH were recorded. Grain yield was highly significant and positively correlated with dry fodder yield (r=0.67), panicle diameter (r=0.50), and plant population at harvest (r=0.50) at 1% significant level. Morphological observations showed diversity among the pearl millet germplasm. Similarly, there was variation between biochemical observations i.e., protein content varied between 9.2–11.5%, total soluble sugars between 1.4–2.6 g 100 g-1, phenolic content between 20.14–34.78 and DPPH scavenging activity varied between 44.18–54.89%. Cluster analysis revealed two major groups, and variability between the expression pattern of these observations. Biochemical profiling supported by heatmap analysis showed considerable diversity, with HHB 299 and Dhanshakti displaying superior protein content, total phenolics, and antioxidant activity, emphasizing their nutritional advantage. The findings emphasize the importance of integrating morphological and biochemical profiling in breeding programs to develop high-yielding, nutrient-rich, and climate-resilient pearl millet cultivars, vital for enhancing food security and public health under challenging agro-climatic conditions.